Carbon balance of rewetted and drained peat soils used for biomass production: a mesocosm study. Issue 5 (2nd May 2016) - Karki, Sandhya; Elsgaard, Lars; Kandel, Tanka P.; Lærke, Poul Erik
Abstract: Rewetting of drained peatlands has been recommended to reduce CO2 emissions and to restore the carbon sink function of peatlands. Recently, the combination of rewetting and biomass production (paludiculture) has gained interest as a possible land use option in peatlands for obtaining such benefits of lower CO2 emissions without losing agricultural land. This study quantified the carbon balance (CO2, CH4 and harvested biomass C) of rewetted and drained peat soils under intensively managed reed canary grass (RCG) cultivation. Mesocosms were maintained at five different groundwater levels (GWLs), that is 0, 10, 20 cm below the soil surface, representing rewetted peat soils, and 30 and 40 cm below the soil surface, representing drained peat soils. Net ecosystem exchange (NEE) of CO2 and CH4 emissions was measured during the growing period of RCG (May to September) using transparent and opaque closed chamber methods. The average dry biomass yield was significantly lower from rewetted peat soils (12 Mg ha −1 ) than drained peat soils (15 Mg ha −1 ). Also, CO2 fluxes of gross primary production (GPP) and ecosystem respiration (ER) from rewetted peat soils were significantly lower than from drained peat soils, but net uptake of CO2 was higher from rewetted peat soils. Cumulative CH4 emissions were negligible (0.01 g CH4 m −2 ) from drained peat soils but were significantly higher (4.9 g CH4 m −2 ) from rewetted peat soils during measurement period (01 May–15 September 2013). The extrapolated annual C balance was 0.03 and 0.68 kg C m −2 from rewetted and drained peat soils, respectively, indicating that rewetting and paludiculture can reduce the loss of carbon from peatlands.